Evaluation of pyraclostrobin and acibenzolar-S-methyl on common bacterial blight of snap bean - Vigo, Sandra Cristina; Maringoni, Antonio Carlos [UNESP]; Camara, Renata de Cássia [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Assays were done under greenhouse conditions in order to evaluate the effect of pyraclostrobin (0.0375, 0.0750 and 0.150 mL.L-1) and acibenzolar-S-methyl (ASM) (0.025 g.L-1) in common bacterial blight on leaves of snap beans cultivar Braganca. These chemicals were sprayed at three different times: five days before; five days before + five days after; and five days after leaf inoculation with an isolate of Xanthomonas axonopodis pv. phaseoli. They were determinate the levels of polyphenoloxidase, peroxidase and total soluble proteins on inoculated and non-inoculated leaves of snap beans sprayed with pyraclostrobin (0.075 g.L-1) and ASM (0.025 g.L-1). All concentration of pyraclostrobin and ASM reduced the area under the disease progress curve (AUDPC) on leaves of snap beans, and the least AUDPC value was observed when this products were sprayed five days before + five days after inoculation. Higher levels of polyphenoloxidase, peroxidase and the total soluble proteins were observed on leaves sprayed with pyraclostrobin or ASM.
Keywords: Phaseolus vulgaris; Xanthomonas axonopodis pv. phaseoli; protein